2014
DOI: 10.1002/jlcr.3213
|View full text |Cite
|
Sign up to set email alerts
|

Efficient syntheses of [11C]zidovudine and its analogs by convenient one‐pot palladium(0)–copper(I) co‐mediated rapid C‐[11C]methylation

Abstract: The nucleosides zidovudine (AZT), stavudine (d4T), and telbivudine (LdT) are approved for use in the treatment of human immunodeficiency virus (HIV) and hepatitis B virus (HBV) infections. To promote positron emission tomography (PET) imaging studies on their pharmacokinetics, pharmacodynamics, and applications in cancer diagnosis, a convenient one-pot method for Pd(0)-Cu(I) co-mediated rapid C-C coupling of [(11)C]methyl iodide with stannyl precursor was successfully established and applied to synthesize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The reaction using five-fold amounts of CuBr/CsF at 80 C afforded (62b) at a much higher yield (83%, Entry 6); however, the reaction produced a large amount of an undesired destannylated product. Considering that the destannylated product (64) is produced by a proton transfer to the transmetallated Cu intermediate (63) from (61b Cu2 ) with the enhanced acidity of the NH proton caused by Cu I coordination to an S atom ( Figure 13), we changed the medium to a much more basic system using a CH 3 I/61b/ [Pd 2 (dba) 3 ]/P(o-CH 3 C 6 H 4 ) 3 /CuCl/K 2 CO 3 (1:25:1:32:2:5) system at 80 C to afford (62b) in nearly quantitative yield (98%, Figure 14) [62]. The desired 11 C-labeled compounds were isolated by preparative HPLC to afford 45% in 42-59% isolated radiochemical yields (decay-corrected).…”
Section: Rapid C-methylation Of Heteroaryl-substituted Stannanes and mentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction using five-fold amounts of CuBr/CsF at 80 C afforded (62b) at a much higher yield (83%, Entry 6); however, the reaction produced a large amount of an undesired destannylated product. Considering that the destannylated product (64) is produced by a proton transfer to the transmetallated Cu intermediate (63) from (61b Cu2 ) with the enhanced acidity of the NH proton caused by Cu I coordination to an S atom ( Figure 13), we changed the medium to a much more basic system using a CH 3 I/61b/ [Pd 2 (dba) 3 ]/P(o-CH 3 C 6 H 4 ) 3 /CuCl/K 2 CO 3 (1:25:1:32:2:5) system at 80 C to afford (62b) in nearly quantitative yield (98%, Figure 14) [62]. The desired 11 C-labeled compounds were isolated by preparative HPLC to afford 45% in 42-59% isolated radiochemical yields (decay-corrected).…”
Section: Rapid C-methylation Of Heteroaryl-substituted Stannanes and mentioning
confidence: 99%
“…In this context, we found that the homocoupling of organocopper, RdCu, can be greatly suppressed by bubbling [ 11 C]CH 3 I in the mixture at lower temperature (À20 C) followed by heating at 80 C for 5 min. Thus, the efficient synthesis of [ 11 C]-62b was possible by the one-pot method, with much higher (double) isolated total radioactivity (7.6 GBq) [63]. The novel one-pot procedure was also applied to the 11 C-labeling of AZT (67), known as an anti-HIV and anti-tumor agent.…”
Section: Rapid C-methylation Of Heteroaryl-substituted Stannanes and mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the Pd 0 ‐mediated rapid C ‐[ 11 C]methylation using organostannane has evolved from the introduction of the [ 11 C]methyl group on the phenyl ring toward its insertion in heteroaromatic, vinyl, and acetyl substituents. The optimized reaction conditions have been applied to the synthesis of PET probes with biological importance such as the [methyl‐ 11 C]thymidine 18 , 4′‐[methyl‐ 11 C]thiothymidine 19 , [ 11 C]zidovudine 20 , [ 11 C]stavudine 21 , [ 11 C]telbivudine 22, [ 11 C]H‐1152 23 , and the 11 C‐labeled GN8 derivative 24 . The congeneric or improved reaction conditions have been adopted by the wider PET chemistry community for the synthesis of important PET probes using the corresponding organostannane substrate, for compounds such as [ p ‐ 11 C‐methyl]MADAM 25 , 5‐[ 11 C]methyl‐6‐nitroquipazine 26 , [ 11 C]toluene 27 , 5‐[ 11 C]methyl‐A‐85380 28 , 4‐[ 11 C]methylmetaraminol 29 , [ 11 C]FMAU 30 , 11 C‐labeled citalopam analogue 31 , 11 C‐labeled mGlu1 antagonist probe 32 , [ 11 C]celecoxib 33 , [ 11 C]M‐MTEB 34 , [ 11 C]MPEP 35 , [ 11 C]SB 222200 36 , (–)‐[ 11 C]OMV 37 , 11 C‐labeled reboxetine analogues 38 and 39 , [ 11 C]CHIBA‐1001 40 , [ 11 C]FTIMD 41 , [ 11 C]metrazoline 42 , [ 11 C]TEIMD 43 , and [ 11 C]ITDM 44 …”
Section: The Discovery Of Pd‐mediated Rapid Cross‐coupling Of [11c]mementioning
confidence: 99%
“…We recently succeeded in the 11 C-labeling of two anti-HIV drugs, to produce [ 11 C]AZT and [ 11 C]d4T, via the Pd(0)-Cu(I) co-mediated rapid C-C coupling reaction (Fig. 1 ) [ 14 ]. These labeled drugs may have potential roles as PET probes, not only in tumor diagnosis, but also in the evaluation of AIDS/HIV infection.…”
Section: Introductionmentioning
confidence: 99%